Comparison of Inflammatory and Angiogenic Factors in the Aqueous Humor of Vitrectomized and Non-Vitrectomized Eyes in Diabetic Macular Edema Patients - Liang, Youling; Yan, Bin; Meng, Zhishang; Xie, Manyun; Liang, Zhou; Zhu, Ziyi; Meng, Yongan; Ma, Jiayue; Ma, Bosheng; Yao, Xiaoxi; Luo, Jing (Frontiers in Medicine, 2021)
Objectives: To compare the aqueous concentrations of inflammatory and angiogenetic factors in vitrectomized vs. non-vitrectomized eyes with diabetic macular edema (DME). Methods: Aqueous samples were obtained from 107 eyes with DME before intravitreal injection of anti-VEGF, 36 eyes with previous pars plana vitrectomy (PPV) combined with pan-retinal endolaser photocoagulation (PRP), and 71 treatment-naïve. Interleukin (IL)-6, IL-8, interferon-induced protein (IP)-10, monocyte chemoattractant protein (MCP)-1, and vascular endothelial growth factor (VEGF) were measured by cytometric bead array (CBA). Optical coherence tomography (OCT) was used for measuring central retinal thickness (CRT). Results: IL-6, IL-8, IP-10, and MCP-1 in aqueous humor of DME vitrectomized eyes were significantly higher than in non-vitrectomized DME eyes, while VEGF was lower than in non-vitrectomized DME eyes. VEGF in aqueous humor significantly correlated with CRT for DME in non-vitrectomized DME eyes. IL-6, IL-8, IP-10, and MCP-1 in aqueous humor were not significantly associated with VEGF for DME in vitrectomized eyes. Conclusions: Inflammation might play an important role in the pathogenesis of DME in vitrectomized eyes. And inflammation might play a central role in the development of DME via the VEGF-independent pathway. Thus, anti-inflammatory therapy might be a strategy for DME in vitrectomized eyes.